2021
DOI: 10.24057/2071-9388-2019-170
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation Of Soil Of The Kola Peninsula (Murmansk Region) Contaminated With Diesel Fuel

Abstract: This work focuses on the creation and use of associations of hydrocarbon-oxidizing microorganisms. Bioremediation of soils with the help of mixed cultural and associations of microorganisms provides wider adaptive possibilities than individual species. This is especially important in conditions of short northern summer. The results of field experiments showed that microbial associations based on indigenous microorganisms (bacteria Pseudomonas fluorescens, P. putida, P. baetica, Microbacterium paraoxydans and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Even low concentrations of diesel can harm plants and soil microorganisms. This is not solely due to the direct toxicity of diesel but also due to the toxic byproducts produced during the microbial breakdown of intermediate hydrocarbons [52][53][54]. When found in soil, diesel can impede the proper functioning of plant cells, resulting in inhibited growth, discolouration, and even death [55].…”
Section: Discussionmentioning
confidence: 99%
“…Even low concentrations of diesel can harm plants and soil microorganisms. This is not solely due to the direct toxicity of diesel but also due to the toxic byproducts produced during the microbial breakdown of intermediate hydrocarbons [52][53][54]. When found in soil, diesel can impede the proper functioning of plant cells, resulting in inhibited growth, discolouration, and even death [55].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of Baikal EM-1 helps to reduce the pH < 7.6-7.7 and increase the RP of Haplic Arenosols, which reduces the rate of oil decomposition. It is obvious that the process of restoring the soil structure disturbed by oil pollution depends on the soil texture composition [35]. Light loamy soils such as Haplic Arenosols contain much less clay and silt in their composition than clay loam soils.…”
Section: Discussionmentioning
confidence: 99%
“…Better performance was shown by the fungal consortium in the biodegradation of n‐alkanes in comparison to the polycyclic aromatic hydrocarbons (El‐Aziz et al, 2021). Results of Korneykova et al (2021) showed that the total petroleum hydrocarbons content was reduced by 82% over 120 days by indigenous microorganisms based microbial associations (bacteria Pseudomonas fluorescens , P. baetica , P. putida , Microbacterium paraoxydans , and fungi Penicillium commune , P. simplicissimum st. 1, and P. canescens st. 1) with mineral fertilizers. Al‐Hawash et al (2019) obtained Aspergillus sp .…”
Section: Mycoremediation Of Organic Pollutantsmentioning
confidence: 99%